Pemberdayaan Peningkatan Kapasitas Wirausaha Desa Melalui Pelatihan Pembuatan Rencana Bisnis - Ahmad Maulana; Nurkardina Novalia; Aslamia Rosa; Dessi Yunita (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: SMEs in Kerinjing Village are faced with the problem of lack of financing and guidance. Efforts are needed tp strengthen these SMEs in facing competition by providing entrepreneurial knowledge sucj as business ethics, handling customer amplaints, and financial management. This community service activity aims to increase the capacity of small business actors in Kerinjing Village. The activities carried out are in the form of business planning training that is beneficial for their business development. Method: The method used in this community service activity is counseling and training. Results: the results of this community service activity are: (1) providing and increasing knowledge about business plan training for SMEs. (2) Increasing interest and desire in entrepreneurship, and (3) providing a forum for distributing products made from community crafts Conclusions: after the activity is carried out, the community gains knowledge, insight and understands the benefits of business planning training. The growing motivation of the community to carry out entrepreneurial activities in improving the welfare of the community.